Estudo fitoquímico de frações do extrato n-butanólico do tubérculo cará-moela (Dioscorea bulbifera) e avaliação das atividades antitumoral e citotóxica - Moreira, Beatriz Godoy Martins (2021)
The planet's biodiversity is immense and can be observed in all environments, it is related to the amount of animals, plants and microorganisms in an area, including aspects of genetic diversity among organisms, and therefore has enormous potential, regarding medicinal exploration in the development of the pharmaceutical industry. However, a major obstacle is the lack of scientific information that correlates, for example, for a given plant species, the biological activity and its chemical constitution, in order to guarantee the efficiency and safety of the use of a plant. Dioscorea bulbifera is a food plant native to Asia and Africa, but it is present in tropical and subtropical regions around the world, developing easily in several regions of Brazil. Recent studies point to a diversity of biological activities exerted by the tubercle cará-moela (D. bulbifera), such as immunomodulating, antioxidant, anti-inflammatory and antitumor action. The drugs currently used to treat cancer are poorly selective, being toxic to tumor cells and normal cells, causing a series of side effects to patients undergoing treatment. With this, there is the expectation of finding substances from plants with potential antitumor action and that are not toxic to healthy cells. The aim of the present study is to study phytochemically the fractions obtained from the n-butanolic extract of D.bulbifera and to investigate the in vitro antitumor activity against leukemic cells and the cytotoxicity in renal cells. Initially, the lyophilized tubers were subjected to cold extraction with 75% ethanol. Once the extract was obtained, it was successively partitioned with the solvents chloroform, ethyl acetate, n-butanol and water, in increasing order of polarity, aiming at pre-purification. The n-butanolic extract was fractionated by a silica flash column giving rise to 11 fractions called F1 to F11. Fractions F5, F6, F7 and F8 were purified through different chromatographic techniques, giving rise to 16 compounds that were submitted to 1H NMR analysis in a Bruker Avance III 500 MHz spectrometer, using deuterated DMSO as solvent. The spectra obtained were evaluated and their data correlated with literature data on compounds previously isolated from D. bulbifera. Through this comparison, it was possible to propose the structure of diobulbinone A, diosbulbin I, diosbulbin J, diosbulbiol B and a para-substituted aromatic compound. The in vitro antitumor activity of the obtained fractions was evaluated against Raji and Jurkat leukemic cells, as well as cytotoxicity against Vero and LLC-MK2 renal cell lines. Fractions F3, F4 and F10 showed good results against the Jurkat cell line with IC50 values below 100 μg mL-1. The F8S2-1 and F8S2-2 subfractions have excellent results with IC50 values of 0.0133 and 21.2332 μg mL-1. With regard to the Raji cell line, the F5, F6, F7, F8 and F11 fractions showed good results, while the F8S2-2 subfraction showed an excellent result, with an IC50 value of 0.3700 μg mL-1. Among them, the F7 showed high Selectivity Index (SI) for the Raji and Jurkat strains when evaluated against the two renal strains (Vero and LLC-MK2). With respect to Raji cells, samples F5, F6, F7 had remarkably high IS values. Fraction F8 is very promising, as it presented high yield and gave rise to two subfractions with excellent antitumor results. With the continuity of studies with D.bulbifera, a possible application of the plant's constituents in drugs that can act selectively in the fight against cancer is expected.